Pengaruh Profitabilitas, Likuiditas, Struktur Aktiva, Pertumbuhan Aktiva, Ukuran Perusahaan Terhadap Struktur Modal - Henry Pratama, Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study is examine the effect of profitability, liquidity, assets structure, assets growth, and firm size on capital structure of manufacture companies listed on Indonesia Stock Exchange for the period 2015-2017. Sample was selected using purposive sampling method amounted to 53 companies. Data processing techniques using multiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) for Windows released 22 and Microsoft Excel 2016. There sul tof this study shows that partially profitability, liquidity have significant effect on capital structure, while assets structure, assets growth, and firm size and tangible have no significant effect on capital structure. However this study shows that simultaneously profitability, liquidity, assets structure, assets growth, and firm size have a significant effect on capital structure